The verbal system in the grammars and manuals of Spanish as a foreign language. Fundamentals and corpus of research - Martínez-Atienza de Dios, María (Círculo de Lingüística Aplicada a la Comunicación, 2023)
In this introduction, we will present the fundamental objective of the research carried out in the articles that make up this monograph, namely: to analyze the relationships that exist between linguistic theory, on the one hand, and the teaching-learning of ELE, on the other. We intend to demonstrate the relevance of theoretical training for ELE teachers, which has an impact on improving learning by students and, in particular, on the development of their metalinguistic competence. For this, we will base ourselves on the analysis of a corpus made up of 55 works, 30 grammars and 25 manuals of levels B2 (15) and C1 (10). The six works of this monograph are integrated into two competitive research projects, whose team the authors are part of.